Pestisida Dan Faktor Risiko Stunting (Kajian Literatur) - Nur Azizah Amalia; Usman; Ayu Dwi Putri Rusman; Rahmi Amir; Haniarti Haniarti (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2023)
The prevalence rate of stunting worldwide in 2020 reached 22% or 149.2 million people. Data from the Indonesian Nutrition Status Study (SSGI) conducted by the Ministry of Health (MoH) reported that in 2021, the prevalence of stunting cases in Indonesia was 24.4%. The purpose of this study is to examine the relationship between pesticide use and the risk of stunting. Using the Literature Review method, various previous studies were analysed that discussed pesticides related to stunting risk factors. Searches were conducted on several databases, namely, Google Scholar, Scopus, Pubmed, and Science Direct. Then the selection was carried out using the PRISMA flow. Based on the results of sorting journal articles, 10 research journal articles were found which were then analysed based on the topic of the study, namely pesticides and stunting. Because pesticides contain Thyroid Disrupting Chemical which can interfere with thyroid hormones, especially in mothers with productive age. Then supported by various other factors that affect stunting caused by pesticide exposure. Therefore, it can be concluded that there is a significant relationship between pesticides and risk factors for stunting.